64.8k views
1 vote
#1 pls thanks ;) . It’s so hard I hate it

#1 pls thanks ;) . It’s so hard I hate it-example-1

1 Answer

2 votes

Given:


\begin{gathered} -a+3b-3c=2\ldots(1) \\ a-2b+3c=-4\ldots(2) \\ -a+2b-c=-2\ldots(3) \end{gathered}

To find a,b,c:

Adding the equations (1) and (2) we get,


b=-2

Adding the equations (2) and (3) we get,


\begin{gathered} 2c=-6 \\ c=-3 \end{gathered}

Subtituting b= -2 and c= -3 in the equation (3) we get,


\begin{gathered} -a+2(-2)-(-3)=-2 \\ -a-4+3=-2 \\ -a-1=-2 \\ -a=-1 \\ a=1 \end{gathered}

Hence the solution is,

a = 1

b = -2

c = -3

User Colemars
by
4.8k points